Surface Plasmon-Polaritons and Transverse Spin Angular Momentum at the Boundary of Hyperbolic Metamaterial with Arbitrary Orientation of the Optical Axis - Belyi, V.; Kurilkina, S.; Kazak, N.; Agabekov, V. (Advanced Electromagnetics, 2017)
The possibility is established and the conditions are found for localization of plasmon-polaritons (PPs) near the boundaries of hyperbolic metamaterials (HMs) of both I and II types with arbitrary orientation of the optical axis. It is grounded that such surface PP has the transverse spin momentum which depends on the wavelength of the exciting wave, the orientation of the optical axis of the hyperbolic metamaterial, and dielectric properties of bordered media.